2020
DOI: 10.1088/2053-1591/ab677a
|View full text |Cite
|
Sign up to set email alerts
|

Structural electronic and dynamic properties of Li3Bi and Li2NaBi

Abstract: We report a study of structural, electronic and dynamic properties of Li 3 Bi and Li 2 NaBi via density functional theory. It is found that Li 3 Bi and Li 2 NaBi show semiconducting property with an indirect electronic band gap. The calculated structural and electronic parameters (lattice parameters, bulk modulus, bulk modulus derivation) are in a good agreement with the available experimental data. Full phonon spectra of Li 3 Bi and Li 2 NaBi materials in the Rock Salt structure were collected using the linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As a result, it is calculated that it will be dynamically stable when 38.42 kbar pressure is applied by using Quantum Espresso software program. Reviews for the Li 3 Bi and Li 2 NaBi compounds have shown that dynamic stability can be achieved with the pressure applied to the Li 2 NaBi compound [25]. This is a So it is seen that frequency of an optic mode is lower than an acoustic mode (LA) for both of the crystals.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, it is calculated that it will be dynamically stable when 38.42 kbar pressure is applied by using Quantum Espresso software program. Reviews for the Li 3 Bi and Li 2 NaBi compounds have shown that dynamic stability can be achieved with the pressure applied to the Li 2 NaBi compound [25]. This is a So it is seen that frequency of an optic mode is lower than an acoustic mode (LA) for both of the crystals.…”
Section: Resultsmentioning
confidence: 97%
“…Guechi et al [24] computed the effect of pressure on phase transition, electronic and optical properties of LiBeX alloys. Erden Gulebaglan and Kilit Dogan [25] reported the structural, electronic and dynamic properties of Li 3 Bi and Li 2 NaBi. They calculated the pressure value that made the Li 2 NaBi alloy dynamically stable.…”
Section: Introductionmentioning
confidence: 99%
“…It is also clear from Figure 6, all the phonon frequencies are positive in the entire Brillouin zone indicating the proposed materials to be dynamically stable. [50,51] The PDC of the considered compounds can be divided into two regions, low-frequency region, and high-frequency region. The low-frequency region extends from 0 to 123.93 cm À1 and 0 to 115.23 cm À1 ; whereas, high-frequency region lies from 138.56 to 152.90 cm À1 and 140 to 156.58 cm À1 for GdPtbi and NdPtBi respectively.…”
Section: Phonon Propertiesmentioning
confidence: 99%